Elevated serum cholesterol levels are associated with proteinuria over 0.5 g/day in premenopausal women with systemic lupus erythematosus. (20th May 2022) - Liu, Haijun; Li, Qianhua; Wei, Xiuning; Ma, Jianda; Long, KangXia; Ouyang, Xia; Liu, Nemin; Li, Yongsheng; He, Liping; Dai, Lie; Cai, Xiaoyan
Background: Systemic lupus erythematosus (SLE) commonly occurs in premenopausal women and is associated with elevated estrogen levels. Patients with SLE may have abnormal serum triglyceride (TG) levels, and lipid reportedly promotes kidney damage in patients with nephrosis. Since estrogen regulates lipid levels, we investigated the serum lipid levels of premenopausal women with SLE and their relationship with proteinuria.Methods: This cross-sectional study included 123 premenopausal women with SLE (SLE group), who were classified into 24-h urine protein exceeding 0.5 g (24 h-UPRO > 0.5 g, n = 22) and 24 h-UPRO ≤ 0.5 g ( n = 101) subgroups, and 100 similarly aged healthy women (control group). Clinical characteristics and biomarker levels were compared between these groups. The associated factors of proteinuria over 0.5 g/day were evaluated using multivariate logistic regression. A receiver operating characteristic (ROC) curve was plotted to assess the cholesterol (CH) cut-off associated with increased development of proteinuria over 0.5 g/day.Results: The SLE group had significantly higher serum TG levels than that of control group. 24 h-UPRO were significantly correlated with serum creatinine, CH, TG, and uric acid levels. Serum CH level was the greatest associated factor for proteinuria over 0.5 g/day. The area under the ROC curve was 0.843, with a CH cut-off of 4.58 mmol/L. Patients with serum CH above 4.58 mmol/L had a higher proportion of type IV LN, but with no statistical difference.Conclusions: In premenopausal SLE patients, serum TG levels were higher than in healthy women, and serum CH levels were the primary associated factor for proteinuria over 0.5 g/day. Proteinura over 0.5 g/day may occur in women with SLE with serum CH levels >4.58 mmol/L. CH levels may be useful for predicting proteinuria.